Identifikasi Pengembangan Produk Pariwisata Perkotaan (Studi Kasus Kota Labuan Bajo) - Luru, Marselinus Nirwan (Jurnal Ilmiah Pariwisata, 2018)
The city is a tourist destination (urban tourism). It is just not a gateway or tourist gathering point. Labuan Bajo has a strategic function and location to become a catchment area for many tourists. However, does Labuan Bajo has urban tourism products so potential as urban tourism? Through a qualitative design with a case study approach, this study find that Labuan Bajo has tourism products that make tourists linger in the city, such as place activity, leisure setting, and municipal service facilities. The tourism product has the role as the main attraction of tourists namely lodging facilities, conferences, entertainment venues (café and bar), shopping facilities (shopping), inter-regional transportation facilities, tourism attractions of Pede Beach, Wae Cicu, Batu Cermin, Puncak Waringin, as well as shopping spaces. And tourism products that support the main activities of tourists in Labuan Bajo, such as transportation facilities, information and travel agents